2015
DOI: 10.1007/s40264-015-0362-0
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk of Hypnotics: Strengths and Limits of Evidence

Abstract: Sleeping pills, more formally defined as hypnotics, are sedatives used to induce and maintain sleep. In a review of publications for the past 30 years, descriptive epidemiologic studies were identified that examined the mortality risk of hypnotics and related sedative-anxiolytics. Of the 34 studies estimating risk ratios, odds ratios, or hazard ratios, excess mortality associated with hypnotics was significant (p \ 0.05) in 24 studies including all 14 of the largest, contrasted with no studies at all suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 80 publications
3
52
0
Order By: Relevance
“…To find 39 of 40 studies showing a positive risk ratio was very highly significant, P<0.000001. Also, the evidence of association satisfied all nine Bradford Hill criteria for inferring causality 12 , though skepticism despite meeting these criteria may be warranted 13 . There remain questions concerning the magnitude of the causality.…”
Section: Risks Of Hypnotic Drugsmentioning
confidence: 93%
See 1 more Smart Citation
“…To find 39 of 40 studies showing a positive risk ratio was very highly significant, P<0.000001. Also, the evidence of association satisfied all nine Bradford Hill criteria for inferring causality 12 , though skepticism despite meeting these criteria may be warranted 13 . There remain questions concerning the magnitude of the causality.…”
Section: Risks Of Hypnotic Drugsmentioning
confidence: 93%
“…There remain questions concerning the magnitude of the causality. The randomized placebo-controlled trials I have suggested would help clarify this causality magnitude 12 .…”
Section: Risks Of Hypnotic Drugsmentioning
confidence: 99%
“…Similarly, the American College of Physicians (ACP) recommended that cognitive behavioral therapy should be the first-choice treatment for insomnia, and the ACP guideline expressed doubt on whether hypnotics were worth the risks, even as secondary choices for short-term use 2,3 .…”
Section: Briefly Summarizing the Risks Of Hypnoticsmentioning
confidence: 99%
“…Indeed, at this writing, there have been 34 epidemiologic studies of hypnotics mortality risks, of which 33 found hypnotics associated with increased mortality (P<0.000001) [4]. One small study demonstrated no general mortality risk, only a cancer mortality risk.…”
mentioning
confidence: 99%
“…Hypnotics still carry no warnings about mortality or cancer risks. Perhaps, despite the strong preponderance of evidence [4], the …”
mentioning
confidence: 99%